ENDOSCOPIC ESOPHAGODIVERTICULOSTOMY IN TREATMENT OF ZENKER’S DIVERTICULUM - A. A. Smirnov; S. U. Dvoreckij; A. V. Prudnikov; A. N. Burakov; S. F. Bagnenko (Вестник хирургии имени И.И. Грекова, 2018)
The objective of the research is to study the efficacy and safety of using a minimally invasive endoscopic method in treatment of Zenker’s diverticulum.Material and methods., 42 patients with a pharyngo-esophageal diverticulum at the age of 59 to 80 years were examined and treated over the two-year period of work. The indication for the operation in all patients was the presence of dysphagia II–IV degree. The method of tunnel dissection in the submucosal layer of esophagus with dissection of the array of cryopharyngeal muscle and endoscopic esophagodiverticulostomy was used. Regardless of the version of endoscopic intervention, the key moment of the operation is the dissection of the cryopharyngeal muscle, which allows to eliminate the fold between diverticulum and esophagus, thus creating a fistula between diverticulum and esophagus.Results. Results of treatment were evaluated clinically, taking into account patients’ complaints and according to the control of X-ray fluoroscopy of esophagus. The patency of esophagus was objectively restored in all cases. Delays of the passage of contrast medium through the esophagus did not occur. Patients did not experience the difficulty in swallowing. Significant complications during the postoperative period were not noted.Conclusions. Endoscopic esophagodiverticulostomy in the treatment of Zenker’s diverticulum is the effective method of treatment. The operational injury is minimal, what reduces the length of stay in hospital. The peculiarity of the method of treatment allows using the early enteral nutrition. The minimally traumatic nature of endoscopic operation and the quickness of its performance allow applying this technique in weak patients, as well as in patients with concomitant pathology.